Post-Partum Prolapse of Genitalia in a Cow - Sahu, Uttam Kumar; Singh, Mayank; Warghat, Chinmay; Khan , Meraj Haider (The Indian Journal of Animal Reproduction, 2025)
Present case report describes resolving a case of postpartum prolapse of genitalia in a cow associated with retention of fetal membrane after medical treatment and manual intervention.